The Effect of Ownership Structure and Leverage Towards Dividend Policy and Corporate Values - Khongrat, Etty; Kusumawati, Andriani; Habsyi, Taber Al; Suharyono, Suharyono (JPAS (Journal of Public Administration Studies), 2021)
This research aims to examine and analyze the effect of Destination Branding on Destination Image. Testing and analyzing the effect of destination branding on destination selection and destination image on destination selection. Meeting planners who live in Jakarta and Bali destination. This research used an explanatory research with simple random sampling technique. Data collection techniques were carried out with questionnaires that distributed to 165 respondents Meeting Planners who lived in Jakarta and Bali. The data analysis used in the study is General Structured Component Analysis (GSCA). The results of this study indicate that the GSCA analysis results have shown that Destination Branding has no significant effect on the Destination Image, with a path coefficient of 0.545 with a value (p-value 0.272> 0.005). The results of the GSCA analysis have proven that Destination Branding has a significant effect on destination selection with a path coefficient of 0.266 and a p-value <0.001. The results of the GSCA analysis have shown that destination image has a significant positive effect on Destination Selection with a path coefficient of 0.299 with a p-value of <0.001.